Nursing practice in relation to older people’s fundamentals of care in nursing homes: An exploratory design - O.M. Nordaunet; E.R. Gjevjon; H. Aagaard; C. Olsson; G. Borglin (International Journal of Nursing Studies Advances)
Background: Nursing practice addressing the physical, psychosocial, and relational needs of older people – the three core dimensions of the fundamentals of care framework along with its overarching dimension, commitment to care – is a complex yet vital aspect of nurses’ scope of practice. However, it is underrepresented in the clinical context of facility-based care, such as nursing homes. Consequently, there is limited understanding of to what extent nurses engage in activities targeting older people’s fundamentals of care needs, the applicability of the framework in practice, and what acts as contextual modulators. Furthermore, contextual modulators of practice require greater attention, especially within increasingly complex healthcare systems, where nursing practice should be studied as a part of a larger system. Objective: To explore nursing practice, its contextual modulators, and the clinical decision-making processes, as aligned with the nursing process of nurses targeting older people’s fundamentals of care needs in nursing homes. Design: An exploratory study. Setting: Four nursing homes across three Norwegian municipalities. Methods: Structured direct observations were conducted. Thus, observations was supported by a protocol developed from established theoretical frameworks and concepts identified in the nursing literature as relevant to practice or as modulators of practice. Data analysis incorporated both textual and numerical analyses in a multimethod approach. Results: A total of 4351 framework activities were observed during 411 sessions (189 hours). On average, nurses engaged in 10.58 activities per observation, often addressing multiple dimensions of the framework simultaneously. Activities related to the dimension commitment to care were less frequently observed than those in the other three dimensions. We found that most observations showed nurses initiating care with activities targeting physical needs, which often expanded to include psychosocial and relational dimensions. Registered nurses primarily focused on the assessment phase of the nursing process. Nursing practice was found to be influenced by a lack of risk management, an unsupportive working environment, and unclear leadership and management of care. Conclusion and implications: This is one of the first studies exploring nursing practice targeting the fundamentals of care framework in this context. We have highlighted the intricate nature of nursing practice, its relationship with clinical decision-making processes, and the functional and performance levels of nursing activities. Contextual modulators were found to negatively influence nursing practice, suggesting the need for improved risk management, a supportive work environment, and clear nursing leadership.